Pengaruh Latihan Kecepatan dan Kelincahan terhadap Menggiring Bola pada Ekstrakurikuler Futsal di SMP Negeri 3 Talang - Khilmi, Muhammad Akhsanul; Sudarmono, Martin (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the effect of speed and agility training on the ability to dribble. This type of research uses experimental research methods regarding causal relationships. The sampling technique uses total sampling. The design in this study used a pre-test and post-test one group. Data analysis techniques use percentages assisted by SPPS. The results of the study can be seen from Speed ​​Training showing that the exercises carried out are able to provide a better change of 8.10% for speed training compared to before being given training. The results of the Agility Training research showed that the exercises carried out were able to provide a better change of 6.34% for agility training compared to before being given training. The results of the dribbling research showed that the exercises carried out were able to provide a better change of 38.95% in the ability to dribble the ball compared to before being given the exercise. The conclusions from this study indicate that there is a significant effect on speed and agility training on the ability to dribble the ball in futsal extracurricular students at SMP N 3 Talang, Tegal Regency.